Old English nominal affixation: A structural-functional analysis* - Vea Escarza, Raquel (Nordic Journal of English Studies, 2016)
This journal article carries out a structural-functional analysis of the formation of Old English nouns by means of affixation. The data comprise a total of 4,370 nouns which result from either prefixation or suffixation, retrieved from the lexical database of Old English Nerthus. Twenty-five derivational functions, inspired by functional grammars and Pounder’s (2000) paradigmatic morphology are proposed to explain the relationship holding between affixes and their bases of derivation. These functions have been divided into split and unified, the former being realized by both prefixes and suffixes and the latter by either prefixation or suffixation. The conclusion is reached that the main target of prefixation is the modification of meaning, in such a way that the meaning of the derivative is less predictable from the input category whereas the main target of suffixation is the change of lexical category, given that the meaning of the derivative is more predictable from the the input category.